PENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN MODEL PEMBELAJARAN COOPERATIVE LEARNING PADA MATERI PROGRAM LINEAR - Hulistiawati Hulistiawati (Jurnal Ilmiah Econosains, 2016)
ABSTRACT This study aims to Know Efekifitas use Linear Model Cooperative Learning Can Improve Learning Outcomes Math Matter Linear Program in class XI AK.2 in SMK Negeri 48 Year 2014. The experiment was conducted in July to December 2014, at SMK Negeri 48 Jakarta. Learning Model for this use is Cooperative Learning, Classroom Action Research, which consists of two cycles, each cycle of meetings held three times and at the third meeting done Post Test. Research has achieved the expected indicators in the second cycle, the number of students who scored to complete the boundary or over at 98, 45% and average value reached 80.79%. Presentation Mastery student has achieved the expected indicators in this study, and students who commit any negative activity does not exceed 35% presentation, but only 2:55%. in Cycle 2 can be argued that student achievement has increased by using model Learning Cooperative Learning It can be concluded that by applying the procedure appropriate CooperativeLearning Learning Model, Can Improve Learning Outcomes Program Linear Mathematical Concepts in Class XI AK 2 SMK Negeri 48 JakartaTahun, 2014. Keywords: Cooperative Learning Model Learning Improve Learning Outcomes.